Factors determining the presence of glass ceiling and influencing women career advancement in Bangladesh - Afza, Syeda Rownak; Newaz, Mohammad Khaleq (BRAC University, 2010)
The purpose of the study is to examine the existence of glass ceiling in different industries and service sectors in Bangladesh. This study also attempts to identify the contributing factors which create the glass ceiling effects and women career advancement in an organization. The analysis of this study indicates five factors responsible for glass ceiling effects which eventually restricts women career opportunity and progression at a certain stage. The identified factors are: management perception, work environment, work life conflict, sexual harassment and organizational policy. From analyzing the data it can be inferred that respondents agreed to some extent about the existence of glass ceiling in their respective organization. According to the respondent's opinion management perception and work environment are most significant factors for creating glass ceiling where as organizational policy and work life conflict are the second most significant factors. On the other hand respondent disagree about sexual harassment as a contributing factor for creating glass ceiling effect in the organization. Whereas pleasant appearance, attitude towards organization, career focused and family support influences career advancement of women in an organization. Implication and areas for future research have also been considered.